Cancer symptom clusters in pediatric patients with cancer undergoing chemotherapy: systematic review protocol (Research, Society and Development, 2023)
This is a systematic review protocol whose objective is to synthesize and evaluate the prevalence, composition, stability, predictors and outcomes of cancer symptom clusters in children and adolescents undergoing chemotherapy. This systematic review protocol is guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols-PRISMA-P. The search for evidence will include MEDLINE/PubMed, Cochrane Library; Embase; PsycINFO and Web-of-Science; plus clinical trial registry websites (ClinicalTrials.gov and WHO-ICTRP) and additional sources: The British Library, Google Scholar, and preprints for Health Sciences-medRXiv. Two researchers will independently extract and evaluate the included studies. The methodological quality of the studies will be assessed using specific tools per study design. The results will be presented through tables, graphs, qualitative synthesis and will be evaluated based on the outcomes. This will be the first systematic review with high methodological rigor to gather evidence on oncological symptom clusters in the area of Pediatric Oncology. Understanding the experiences of children and adolescents with cancer on oncological symptom clusters can provide a scientific basis for directing personalized therapies, especially for the management of concomitant symptoms.